Postnatal high-fat diet leads to spatial deficit, obesity, and central and peripheral inflammation in prenatal dexamethasone adult offspring rats. Issue 11 (3rd August 2016) - Hsieh, Chih-Sung; Li, Shih-Wen; Sheen, Jiunn-Ming; Yu, Hong-Ren; Tiao, Mao-Meng; Tain, You-Lin; Su, Chung-Hao; Huang, Li-Tung
Abstract : Synthetic glucocorticoids are frequently used in clinical practice for treating pregnant women at risk of preterm delivery, but their long-term effects on the infant brain are largely unknown. Pregnant Sprague–Dawley rats were administered vehicle or dexamethasone between gestational days 14 and 21. Male offspring were then weaned onto either a standard chow or a high-fat diet. The postnatal levels of insulin-like growth factor I (IGF-1), tumor necrosis factor-α (TNF-α), and asymmetric dimethylarginine (ADMA) in the plasma, liver, and brain were examined, as well as the possible effects of prenatal dexamethasone on cognition. We found that a postnatal high-fat diet led to spatial deficits detected by the Morris water maze in adult offspring administered dexamethasone prenatally. The spatial deficit was accompanied by decreased IGF-1 mRNA and increased ADMA levels in the dorsal hippocampus. In peripheral systems, a postnatal high-fat diet resulted in decreased plasma IGF-1, increased plasma corticosterone, increased concentrations of transaminases, TNF-α mRNA, and ADMA in the liver, and associated obesity in adult offspring administered prenatal dexamethasone. In conclusion, a postnatal high-fat diet led to spatial deficits, obesity, and altered levels of IGF-1, TNF-α, and ADMA in the plasma, liver, or brain.